Performance of Carbon Nanotube on Nickel-Plated Copper Substrate Using Electrophoretic Deposition Process for Electronic Cooling Application: Response Surface Method Optimization - Bahru R.; Zamri M.F.M.A. (Springer Nature, 2025)
Thermal interface materials (TIMs) have emerged as a potential material for heat dissipation in the cooling system due to their good materials in heat transfer and help protect devices from damage. The main challenge of TIMs is the lower thermal conductivity of materials and poor surface contact, resulting in high internal thermal resistance. Therefore, carbon nanotubes (CNTs) are the best candidate due to their good thermal conductivity. However, the method for deposition of CNTs on the substrate involves high operating temperature and produces unwanted impurities. This study introduces electrophoretic deposition due to the convenient process with operation at room temperature, fast deposition time, simple equipment setup and production of fewer impurities. Pristine CNTs were deposited on the nickel-plated copper substrate using a direct current. The deposition yield can be varied by the variation of CNT-solvent concentration (< 1.0mg CNT/ml) and applied voltage. The interaction between parameters of electrophoretic deposition (EPD) was optimized using Design of Experiment (DOE) software through the response surface method (RSM) to have maximum deposition of CNTs. Field emission scanning electron microscopy (SEM) was performed to analyze the surface morphology of the deposition and observe the maximum thickness of 56.95m with 11.0mg of CNTs deposited on nickel substrate when operated under 175V applied voltage, 10min deposition time for 0.50mg/ml concentration. ? King Fahd University of Petroleum & Minerals 2024.